Repetitive transcranial magnetic stimulation associated with antidepressant: start and intensive of the antidrepressant answer (Archives of Clinical Psychiatry, 2004)
OBJECTIVE: Transcranial magnetic stimulation has been developed as a noninvasive method to stimulate the cortex, and the treatment of depression is one of its potential therapeutic applications. This report makes a review about add-on trials (hf-rTMS plus antidepressants) discuss whether rTMS does accelerate the onset of action, and increase the therapeutic effects of antidepressants. METHOD: The authors review controlled studies of nonconvulsive rTMS therapy for depression associated with antidepressants. In addition, the authors presented a randomized, double-blind, unicentric trial performed at Institute of Psychiatry of Faculty of Medicine of University of São Paulo with patients meeting DSM-IV criteria for non-psychotic severe depressive episode in order to assess if hf-rTMS augments and accelerates the onset of action of amytriptiline. RESULTS: Most data support an antidepressant effect of high-frequency repetitive TMS administered to the left prefrontal cortex. The absence of psychosis might predict treatment success. Technical parameters possibly affecting treatment success include intensity and duration of treatment, but these suggestions require systematic testing. CONCLUSIONS: rTMS shows promise as a novel antidepressant treatment. Systematic and large-scale studies are needed to identify patient populations most likely to benefit and treatment parameters most likely to produce success. In addition to its potential clinical role, TMS promises to provide insights into the pathophysiology of depression through research designs in which the ability of rTMS to alter brain activity is coupled with functional neuroimaging.